Heutagogy in Research-Based Learning at Sanggar Anak Alam (SALAM) Yogyakarta - Setyoningrum, Indri Ajeng (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study described the design of the heutagogy approach applied at Sanggar Anak Alam (SALAM) Yogyakarta. Heutagogy is the study of self-determined learning. Heutagogy provides opportunities for students to choose what to learn and how to learn it freely. SALAM is one of the alternative schools that has applied the concept of a heutagogy approach for a long time. The learning model used by the SALAM learners is research-based learning. This research design is qualitative with a descriptive type of research where data collecting from interviews, observations, field notes, and personal documentation described in the form of descriptive narratives. The research findings show that SALAM applies the design concept of a heutagogy approach in the research-based learning process which includes self-determination of learning contracts, flexible curriculum formation, self-directed questions, flexible and negotiable assessments, reflective exercises, and collaborative learning. Through a heutagogy approach with research-based learning, SALAM students can face the challenges of the 21st century needs.